2000
DOI: 10.1074/jbc.m005872200
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of the Conserved Thr247 Residue in the Functioning of the Osmosensor EnvZ, a Histidine Kinase/Phosphatase, in Escherichia coli

Abstract: The histidine kinase/phosphatase EnvZ helps Escherichia coli adapt to osmotic shock by controlling the phosphorylation state of the transcription factor OmpR, which regulates the levels of the outer membrane porin proteins OmpF and OmpC. We examined the effects of mutating the highly conserved

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
70
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 54 publications
(63 reference statements)
7
70
0
1
Order By: Relevance
“…The activated regulator protein then triggers expression of specific target genes. Many histidine kinases also possess phosphatase activities that allow dephosphorylation and hence inactivation of the regulator protein (37). In the case of EnvZ/OmpR, the level of phosphorylation of OmpR is important for the tight control of osmoregulation (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activated regulator protein then triggers expression of specific target genes. Many histidine kinases also possess phosphatase activities that allow dephosphorylation and hence inactivation of the regulator protein (37). In the case of EnvZ/OmpR, the level of phosphorylation of OmpR is important for the tight control of osmoregulation (40).…”
Section: Discussionmentioning
confidence: 99%
“…According to sequence analysis, CzcS, like EnvZ in Escherichia coli, belongs to class I histidine kinases. In this class the catalytic and ATP-binding domain is separated in two regions (37). The A domain is involved in the dimerization, phosphotransfer, and phosphatase activity, while the B domain binds ATP (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Point mutations within a related bacterial HK, EnvZ, have been identified that affect the kinase activity, the phosphatase activity, or both enzymatic activities of this bifunctional enzyme. Based on current work characterizing the effects of point mutations on the enzymatic activity of EnvZ (Dutta and Inouye, 1996;Hsing et al, 1998;Dutta et al, 2000), however, it is not possible to predict how an amino acid substitution of a Phe residue for Leu 453 would affect CRE1 expression or function in vivo. Examination of the sequencing chromatograms revealed that the single base change detected in the CRE1 coding sequence was found in a homozygous rather than heterozygous state (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…(lanes [25][26][27][28] with all the other experiments], the reason for which is not known at present.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm the above conclusions further, we took advantage of an EnvZc mutant, T247Y, which has kinase activity but lacks phosphatase activity (26). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%